2019
DOI: 10.3390/toxins11010043
|View full text |Cite
|
Sign up to set email alerts
|

The Individual and Combined Effects of the Cyanotoxins, Anatoxin-a and Microcystin-LR, on the Growth, Toxin Production, and Nitrogen Fixation of Prokaryotic and Eukaryotic Algae

Abstract: Globally, eutrophication and warming of aquatic ecosystems has increased the frequency and intensity of cyanobacterial blooms and their associated toxins, with the simultaneous detection of multiple cyanotoxins often occurring. Despite the co-occurrence of cyanotoxins such as microcystins and anatoxin-a (ATX) in water bodies, their effects on phytoplankton communities are poorly understood. The individual and combined effects of microcystin-LR (MC-LR) and ATX on the cyanobacteria Microcystis spp., and Anabaena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 75 publications
0
23
0
2
Order By: Relevance
“…Animals reportedly die from exposure to ANTX-a following toxic response to acetylcholine receptor inhibition at neuromuscular junction (Carneiro et al, 2015). Chia et al (2019) revealed that high-dose injection or ingestion of ANTXa can cause fatal suffocation in mammals and induces oxidative stress. The influence of ANTX-a on the biological nervous system has been extensively investigated because ANTX-a is toxic to this system; nervous system diseases are characterized by disordered muscle bundles, decreased motor ability, tremor and gait changes, irregular breathing (Rymuszka and Sieroslawska, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Animals reportedly die from exposure to ANTX-a following toxic response to acetylcholine receptor inhibition at neuromuscular junction (Carneiro et al, 2015). Chia et al (2019) revealed that high-dose injection or ingestion of ANTXa can cause fatal suffocation in mammals and induces oxidative stress. The influence of ANTX-a on the biological nervous system has been extensively investigated because ANTX-a is toxic to this system; nervous system diseases are characterized by disordered muscle bundles, decreased motor ability, tremor and gait changes, irregular breathing (Rymuszka and Sieroslawska, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of industries and agriculture has led to the increasing discharge of wastewater containing nitrogen and phosphorus into water bodies. These activities may result in eutrophication and development of cyanobacterial blooms [1,2]. The monocyclic heptapeptide microcystins (MCs) are the secondary products of cyanobacteria metabolism and most harmful cyanotoxin found in water bodies [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Chia et al [ 145 ] studied the effects of the cyanotoxins ATX-a and MC-LR as single toxins and combinations of both (25 µg L −1 each) on Microcystis spp., T. variabilis and the green alga Selenastrum capricornutum . Following exposure to the cyanotoxins, ATX-a or MC-LR, the growth of Microcystis LE-3 was inhibited.…”
Section: Cyanotoxins and Interspecies Interplaymentioning
confidence: 99%
“…These data demonstrated the diverse effects of cyanotoxins on the growth and physiology of phytoplankton species, which may explain the succession of the green algae following the collapse of toxic cyanobacterial blooms. Even though species-specific effects related to the cyanotoxins individually and combined were observed, the effects of the combined toxins on some strains were greater than with single toxin exposures [ 145 ].…”
Section: Cyanotoxins and Interspecies Interplaymentioning
confidence: 99%